Personal and impersonal sentences in Lithuanian and Proto-Indo-European - Kortlandt, Frederik (Vilnius University Open Series, 2022)
The dative subject construction of the historical languages is the continuation of the Proto-Indo-European thematic present. It was largely replaced by the construction with a nominative subject that continued the athematic present as well as the aorist, where the ergative was reinterpreted as a nominative.